Avicenna and Thomas Aquinas on Natural Prophecy - López-Farjeat, Luis Xavier (My University, 2014)
In De Veritate, question 12, article 3, Thomas Aquinas discusses whether prophecy is natural. Given that there he argues that prophecy is a divine gift , he seems to break away from the Muslim philosopher Avicenna, who holds a naturalistic explanation of this phenomenon. Certainly Avicenna explained prophecy in psychological and metaphysical terms, and was considered by some Christian theologians as proponent of a naturalistic view, thought to be incompatible with prophecy conceived as a divine and supernatural gift. In this paper I trace the origin of the discussion on whether prophecy is natural or supernatural, and then I recapitulate Avicenna’s understanding of this phenomenon in two short treatises, namely, the Epistle Concerning Dreams and On the Proof of Prophecies, and in the De anima and the Metaphysics of his major work The Book of Healing. Then I review Aquinas’s understanding of Avicenna’s view and his own conception of “natural prophecy” in order to show that, although when he argues for the divine origin of prophecy he distances himself from the Persian philosopher, he sees in his interpretation of Avicenna’s naturalistic doctrine a theory that could explain why some people sometimes attain knowledge of future events through a natural process different from divine prophecy. Finally, I discuss for what purpose Aquinas would have admitted this naturalistic view